Fat-forming variant of solitary fibrous tumour of the pleura: CT findings - Park, C Y (The British Institute of Radiology., 2011)
The fat-forming variant of solitary fibrous tumour (SFT) was previously called lipomatous haemangiopericytoma and is a rare variant of solitary fibrous tumour. It predominantly occurs in the deep soft tissues of the retroperitoneum and thigh. Only a handful of cases involving the perineum, spine, thoracic wall and pelvic cavity have been reported in the radiological literature and the fat-forming variant of SFT involving the pleura has not been previously reported. Herein, we report the CT findings of a case of the fat-forming variant of SFT involving the pleura that was treated by excision. Chest CT showed a large lobulated heterogeneous fatty mass with a multifocal enhancing soft-tissue component in the left lower hemithorax. Although rare, the fat-forming variant of SFT of the pleura should be added to the differential diagnosis of fat-containing pleural soft-tissue tumours.